O Conselho Ultramarino e sua pauta: aspectos da comunicação política da monarquia pluricontinental (1640-1668) – notas de pesquisa - Marcello José Gomes Loureiro (Nuevo mundo - Mundos Nuevos, 2013)
The analysis of the political communication between the Overseas Council and the Portuguese America can contribute not only to the understanding of the political agenda of this Council and local elites, but also it allows us to reach a better knowledge of the formation processes of the Portuguese overseas policy. The purpose of this article is to present preliminary results, especially quantitative, of the investigations carried out around this political communication, in a critical conjuncture, such as the post-Restoration of Portuguese monarchy (1640-1668).